Feasibility and reliability of the Functional Movement Screen battery in adults with intellectual disability. Issue 6 (7th February 2022) - Sanchez‐Lastra, M.A.; Moldes, J. Marín; Diz, J.C.; Martínez‐Lemos, R.I.; Ayán, C.
Abstract: Background: The feasibility and reliability of the Functional Movement Screen (FMS) battery for predicting injury risk have been widely studied in athletic, military, public service and healthy populations. However, scant research has been carried out in people with disabilities. This study aimed at identifying the feasibility and reliability of the FMS battery when administered to adults with intellectual disability (ID). Methods: Adults from a residential and day care centre over 18 years of age, diagnosed with ID and able to follow simple instructions, were included in the study. All participants with behavioural or health problems that prevented the completion of the FMS battery were excluded. All exercises were video recorded to assure proper scoring. Three assessors (one trained and two novices) scored each of the FMS subtests performed separately from the videos. Feasibility was based on completion rates. Reliability of the composite test scores was analysed using intraclass correlation coefficients (ICCs). Results: A total of 30 people with ID (mean age: 35.5 ± 7.12 years; 33.3% women) completed all assessments. The battery showed to be feasible, although difficulties when performing two of the subtests were observed among those with moderate and severe ID. Mean total scores from the three assessors ranged from 7.83 to 8.90. An inverse trend was observed indicating that the higher the ID level, the lower the total FMS score. Test–retest reliability was good for the trained assessor (ICC = 0.89) and mostly moderate for both novice assessors (ICC range: 0.60 to 0.76). Moderate to good inter‐rater reliability was observed (ICC range: 0.65 to 0.80). Conclusion: The FMS battery is a reliable tool that can be performed by people with ID, albeit with certain difficulties, especially in those with moderate to severe impairment. The battery does not seem to be useful for identifying people with ID at risk of suffering a sport injury. Adequately powered, well‐designed studies are required to determine if the FMS battery is appropriate for identifying changes in functional performance in this population.